Introduction - Siobhán O’Gorman; Elaine Sisson; Ian R. Walsh (Review of Irish Studies in Europe)
RISE 4.1 examines the complex interplay between Irish and European culture via the  Dublin Gate Theatre  from its founding in 1928 to the present day. The issue explores Irish presentations of European work and Irish theatre that connects variously with Europe.  But it also shows how the Gate's prioritisation of excellence in directing, design, and adaptation positions the Gate within wider networks of European artistic exchange. The articles in this issue question how such exchange in its diversity of thought and practice has allowed for greater inclusivity of marginalised groups but has also led to elitism and exclusion.